Historical maps improve the identification of forests with potentially high conservation value - Grabska‐Szwagrzyk, Ewa; Jakiel, Michał; Keeton, William; Kozak, Jacek; Kuemmerle, Tobias; Onoszko, Kamil; Ostafin, Krzysztof; Shahbandeh, Mahsa; Szubert, Piotr; Szwagierczak, Anna; Szwagrzyk, Jerzy; Ziółkowska, Elżbieta; et al. (Conservation letters, 2024)
The EU Biodiversity Strategy 2030 aims to better protect natural ecosystems with high biodiversity and climate change mitigation potential. To achieve this goal, it is crucial to identify forests worth protecting, such as those characterized by long continuity and old age. Here, we propose a robust approach that combines historical maps from the mid‐19th century with remote sensing data to identify areas that have been forested for over 150 years, aiming to reduce the need for detailed and time‐consuming field investigations in potential conservation areas. We tested this approach in a 20,000 km2 region in the Polish Carpathians, an area likely containing many unprotected forests of high conservation value, where historical maps from the mid‐19th century are representative of much of Central Europe. Our results showed that an area of approximately 4200 km2 has been continuously forested since at least the mid‐19th century. Currently, 50% of these forests are outside protected areas, representing an important conservation opportunity. More generally, our approach can support the identification of valuable forests worth protecting before they are lost and provide useful insights for policymakers and stakeholders in the ongoing debate on the challenges of improving forest conservation in the Carpathians, and Europe more widely.